Calcium sulphate, phosphogypsum and calcium carbonate in the amelioration of acid subsoils for root growth - Carvalho, M.C.S.; van Raij, B. (Plant and soil, 1997)
The chemical barrier to root development existing in the subsoils of acid soils is a subject of increasing interest. In order to better understand the factors involved in the amelioration of subsoil acidity, the effects of calcium sulphate, phosphogypsum and calcium carbonate on the properties of the solid and liquid phases of subsoil samples and on the growth and nutrient uptake by maize (Zea mays L.) were evaluated. The soils used were two alie red-yellow latosols, two acric dusky red latosols and one alie dark-red latosol from the State of São Paulo, Brazil. A vertical split-root technique was used in a greenhouse experiment, with the plants initially grown in a small pot with 130 g fertile soil, which was introduced in a larger pot containing 2 dm 3 of the subsoil samples. The treatments consisted of a control (C) and applications of calcium carbonate (CC), calcium sulphate (CS) and phosphogypsum (PG) at the rate of 10 mmolc Ca²⁺ dm⁻³. CS and PG reduced soil acidity, but in a much smaller proportion than CC. Calcium carbonate reduced the activity of Al³⁺ because of the increase in pH. Total aluminum and calcium contents in the soil solution were much higher for the red-yellow latosols than for the other soils, indicating lower sorption of Ca²⁺ and $SO_4^{2 - }$ in these soils. The activity of Al in the soil solution was decreased in different ways for the five soils, depending on the ionic strength and the formation of the ionic pair $AlSO_4^ + $ and, in the case of PG, the formation of complexes of Al with F (AlF²⁺, $AlF_2^ + $ and $AlF_3^0$). The subsoil samples presented severe restrictions for maize root growth and all three treatments were equally effective in increasing root development, which could be attributed to the supply of calcium in one of the acric dusky red latosols and a combined effect of the amendment in reducing the activity of Al and increasing the activity of Ca in the soil solution in the other soils. As a consequence the three treatments increased in the same manner water, N and K uptake from the subsoil and the dry matter production of maize. It can be concluded that, for the soils considered in this research, phosphogypsum is an effective amendment for acid subsoils containing low calcium or toxic aluminum contents.